INOVASI GURU IPS DALAM MENGIMPLEMENTASIKAN STRATEGI OUTDOOR LEARNING PADA PEMBELAJARAN IPS KELAS III SDN 05 SUNGAI JAMBU - Rama Sofiani; Resti Auzi Ilmiah; Randi Febrian; Nurhanifa; Rizka Agraysia; Susi Ratna Sari (STKIP Subang, 2026)
This study aims to describe the innovation of social studies teachers in integrating outdoor learning strategies in grade III of SDN 05 Sungai Jambu. The background of this study is the low student interest and the dominance of lecture-based learning methods, which make students difficult to understand concepts concretely. This research uses a descriptive qualitative approach. Data were collected through observation, interviews, and documentation. The results show that teachers utilize the surrounding environment, including tofu and tempeh production sites, as learning resources. The implementation of outdoor learning increases student activeness, motivation, cooperation, and understanding of social studies concepts. Obstacles such as time management and supervision can be overcome through proper planning. Therefore, outdoor learning strategies are effective in improving meaningful learning in elementary schools Penelitian ini bertujuan untuk mendeskripsikan inovasi guru IPS dalam mengintegrasikan strategi pembelajaran outdoor di kelas III SDN 05 Sungai Jambu. Permasalahan penelitian ini adalah rendahnya minat belajar siswa serta dominasi metode ceramah dalam pembelajaran IPS. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa guru memanfaatkan lingkungan sekitar sebagai sumber belajar kontekstual. Penerapan pembelajaran outdoor mampu meningkatkan keaktifan, motivasi, kerja sama, serta pemahaman siswa. Dapat disimpulkan bahwa strategi pembelajaran outdoor efektif dalam meningkatkan kualitas pembelajaran IPS di sekolah dasar